2015
DOI: 10.1038/ajg.2015.284
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Patients Are at Increased Risk of Invasive Pneumococcal Disease: A Nationwide Danish Cohort Study 1977–2013

Abstract: The risk of IPD is significantly increased both before and after diagnosis of IBD, with limited impact of IBD medications. This suggests that the risk of IPD in patients with IBD is related to the underlying altered immune response in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 26 publications
1
52
0
1
Order By: Relevance
“…A large recent study demonstrated that IBD patients had an increased risk of invasive pneumococcal pneumonia both before and after the diagnosis of IBD. In this study, the risk of pneumonia was high even in patients with limited IBD medications, suggesting that the risk is related to the underlying alternation in the immune response and not immunosuppressive therapy itself [26]. Furthermore, IBD patients who are hospitalized for pneumonia are at an increased risk for death during the hospitalization [27].…”
Section: Pneumococcal Diseasesmentioning
confidence: 84%
“…A large recent study demonstrated that IBD patients had an increased risk of invasive pneumococcal pneumonia both before and after the diagnosis of IBD. In this study, the risk of pneumonia was high even in patients with limited IBD medications, suggesting that the risk is related to the underlying alternation in the immune response and not immunosuppressive therapy itself [26]. Furthermore, IBD patients who are hospitalized for pneumonia are at an increased risk for death during the hospitalization [27].…”
Section: Pneumococcal Diseasesmentioning
confidence: 84%
“…Similarly, an increased frequency of tonsillectomies 210 has been reported in CD and this may be an indication of recurrent pharyngitis. A further indication of a predisposition to infection in CD comes from the demonstration that these patients are more susceptible to invasive pneumococcal infection 211 .…”
Section: The Three Phases Of Crohn’s Diseasementioning
confidence: 99%
“…This suggests that the risk of IPD in patients with IBD is related to the underlying altered immune response in these patients [11]. Also, lowest income UC patients were shown to have higher adjusted odds for influenza virus infection, and additionally H. influenzae may be another cause for pneumonia among IBD patients [12]. CMV pneumonia should always be suspected in IBD patients who present fever and tachypnea, especially if the latter is worsening and/or is associated with dyspnea.…”
Section: Pulmonary Infections In Ibdmentioning
confidence: 99%